Peningkatan Kualitas Pembelajaran Tematik melalui Model Discovery Learning Berbasis HOTS pada Peserta Didik Kelas V SD Negeri 1 Metro Utara - Gustin Rif’aturrofiqoh (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
The problem of this research is about the one-way teaching and learning process, the teacher's teaching methods are less attractive, the learning is still conventional and the percentage of students' learning completeness at SDN 1 Metro Utara is low. The purpose of this study was to determine the improvement of the quality of thematic learning of students through the Discovery model in Class V students of SDN 1 Metro Utara for the 2020/2021 academic year. The method used is a classroom action research method which consists of three cycles. Each cycle consists of stages of planning, implementing actions, observing and reflecting. Collecting data using tests, documents and observations. The results showed that the application of the Discovery Learning model could increase students' learning activities. In the first cycle the number of students who completed as many as 12, and in the second cycle as many as 22 and the third cycle as many as 26 students. Meanwhile, the percentage of student activity in cycle I was 43%, Cycle II was 78.5% and Cycle III was 92.8% increased by 48.2% ("Very Active" category).